Estudo de concretos com adição de nanosílica submetidos à ação combinada de cloretos e CO2 - Santos, Mariane Oliveira dos (2019)
Corrosion of reinforcement is one of the most severe pathological manifestations that can affect reinforced concrete structures, and the main aggressive agents of corrosion are chloride and CO2. Chlorine ions can cause corrosion even in situations in which the concrete is alkaline and the action of the CO2 results in the carbonation, that is the responsible for the despassivation of reinforcement. The study of these aggressive agents in an isolated manner is widely exploited, existing consensus in the results obtained in the experimental research. However, the study of the combined action is something more recent and yet there is not agreement in the obtained results, as the influence of the conjoint action of these aggressive agents in the durability of the reinforced concrete structures. Concurrently with this question, there is the need of to attain more durable concrete structures and, for this, incorporations are made to the concrete. Among the most used additions one could mention the active silica and most recently, with the advance of the nanotechnology, the nanosilica. These addictions promote the filling effect and pozzolanic effect in the cement matrix, resulting in a more durability of the concrete structure. This research was developed with the main objective of evaluating the behavior of the concretes with nanosilica addiction, when subjected the combined action of the chloride ions and the CO2. To achieve this, concrete cylindrical specimens were molded, in two relations water/binder ratios, 040 and 0,56. Concretes with the incorporation of 0%, 1%, 5% and 10% of nanosilica colloidal and 10% of active silica were studied. It was used superplasticizer additive only in the concretes with relation water/binder ratio 0,40 and the content to be used was determined by means of a consistency test, being fixed in (230±10) mm. Firstly, the concretes were subjected to tests of resistance to compression and absorption of water by concrete capillarity and, in both, the better results were presented by the concretes with the relation equal to 0,40, with the most efficient use being 10% of nanosilica. Sequentially, the concretes were subjected to durability tests, CO2 action and the attack of chlorides in isolated and combined form. In the accelerated carbonation tests, only the concretes with water / agglomeration relation equals to 0.56 presented a carbonation front, which occurred after 140 days of testing. The greatest advance of the carbonation front was verified in the tracing with the incorporation of 1% of nanosilica and 10% of active silica. In the combined tests, of chloride/accelerated carbonation, it was possible to verify the presence of carbonation front only in the concretes with water / agglomeration relation equals to 0.56, however, the fact happened faster, after 84 days in carbonation chamber. Hence, it can be concluded that the chlorine ions acted accelerating the carbonation process of the concretes. Both in isolated chloride tests and in the combined ones, in all the water / agglomeration relations studied, the use of mineral additives led to a reduction in the penetration depth of chlorine ions, with the addition of 10% of nanosilica being the most efficient. Comparing the isolated and combined tests, it is concluded that the CO2 acted contributing to a smaller advance of the chlorine ions in the concretes studie.